2019
DOI: 10.3389/fnhum.2019.00094
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Neural Correlates of Empathy and Anxiety During Socioemotional Processing

Abstract: Empathy is characterized by the ability to understand and share an emotional experience with another person and is closely tied to compassion and concern for others. Consequently, this increased emotional awareness and sensitivity may also be related to increased anxiety. Taken from another perspective, higher general anxiety may translate into increased concern for others, or concern for how one’s actions might affect others, and therefore may be linked to increased empathy. Furthermore, self-reflection is po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 76 publications
1
13
0
1
Order By: Relevance
“…On the other hand, we found that individuals with higher IRI empathy scores reported higher scores on the anxiety, depression and post-traumatic stress disorder scales. Analogous results were found in a study investigating the overlapping neural network between empathy and anxiety ( 50 ). Moreover, another study found that adults who had experienced trauma during childhood reported greater empathy, compassion, and prosocial behavior ( 51 ).…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, we found that individuals with higher IRI empathy scores reported higher scores on the anxiety, depression and post-traumatic stress disorder scales. Analogous results were found in a study investigating the overlapping neural network between empathy and anxiety ( 50 ). Moreover, another study found that adults who had experienced trauma during childhood reported greater empathy, compassion, and prosocial behavior ( 51 ).…”
Section: Discussionsupporting
confidence: 84%
“…Self-reflection, compared with reflecting on the other persons and to a major part also compared with perceiving photographs of one-self, was associated with more prominent dorsomedial and lateral prefrontal, insular, anterior and posterior cingulate activations (Herwig et al, 2012). And the brain mechanism of the anxiety process that is associated with anxiety related to bilateral insula activation, and worry related to medial prefrontal cortex activation (Knight et al, 2019).…”
Section: Self-reflectionmentioning
confidence: 98%
“…Thus, perspectivetaking with self-other distinction is a social cognitive process that could inherently regulate affective processes including psychophysiology. In addition, right TPJ activity during emotion introspection has been associated with trait-level affective empathy (Knight et al, 2019), further suggesting that right TPJ functioning may play a role in affective aspects of empathy. However, at the neural level, the potential role of the right TPJ in modulating physiological activity in response to others' emotional suffering has yet to be examined.…”
Section: Introductionmentioning
confidence: 97%